Case report: Near-complete response to neratinib-based treatment in HR-positive HER2-amplified metastatic breast cancer refractory to trastuzumab deruxtecan - Tokat, Ünal Metin; Adibi, Ashkan; Aydın, Esranur; Bilgiç, Şevval Nur; Özgü, Eylül; Tutar, Onur; Demiray, Mutlu (Frontiers in Oncology, 2025)
Breast cancer (BC) is the leading cause of cancer-related mortality among women. The backbone of first-line treatment in HR+/HER2+ BC is dual anti-HER2 blockade combined with taxane chemotherapy. Although this regimen exhibits high rates of response and disease control in both HR+ and HR− cohorts, some patients could have intrinsic or develop acquired resistance to trastuzumab and/or pertuzumab. Here, we achieved a near-complete response in HR+ HER2-amplified and overexpressing metastatic BC twice through molecular tumor board (MTB) discussions: initially, with trastuzumab deruxtecan (T-DXd) when HER2 IHC was positive, and, then, with neratinib plus fulvestrant plus paclitaxel when IHC was negative. Our case presents GATA3 and NOTCH2 mutations, MCL1 and CKS1B amplifications, as well as ERBB3/KRAS overexpression and ER signaling as potential new mechanisms of resistance to T-DXd. Furthermore, we demonstrated that triplet combination could induce a remarkable response in the T-DXd–refractory setting, which could be explored in future clinical trials in HR+ and HER2-activated (by RNA or protein overexpression, amplification, and mutation) patients. Our case also highlights the importance of the MTBs to dynamically and reactively manage the course of disease and treatment on a per-patient basis.